2020
DOI: 10.1093/aob/mcaa204
|View full text |Cite
|
Sign up to set email alerts
|

Selective pollination by fungus gnats potentially functions as an alternative reproductive isolation among fiveArisaemaspecies

Abstract: Background and Aims Interspecific difference in pollinators (pollinator isolation) is important for reproductive isolation in flowering plants. Species-specific pollination by fungus gnats has been discovered in several plant taxa, suggesting that they can contribute to reproductive isolation. Nevertheless, their contribution has not been studied in detail, partly because they are too small for field observations during flower visitation. To quantify their flower visitation, we used the genus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…It is not known whether Ditassa flowers are deceptive. Representatives of deceptive and pollinator-trapping plant species in other families, such as Aristolochiaceae ( Aristolochia ; [ 25 , 26 , 27 ]), Araceae ( Arisaema ; [ 28 , 29 , 30 , 31 , 32 ]), and orchids (e.g., Pleurothallis [ 33 ], Trichosalpinx [ 34 ], Lepanthes [ 35 ], Pterostylis [ 36 , 37 ]) are likewise known to be visited/pollinated by Phoridae ( Megaselia ), Sciaridae ( B radysia , Corynoptera , Pseudolycoriella ), Chloropidae ( Oscinimorpha ), and Ceratopogonidae ( Forcipomyia ). Furthermore, various economically important crops (e.g., Cacao; [ 38 ]) depend on the same dipteran families and genera for pollination.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known whether Ditassa flowers are deceptive. Representatives of deceptive and pollinator-trapping plant species in other families, such as Aristolochiaceae ( Aristolochia ; [ 25 , 26 , 27 ]), Araceae ( Arisaema ; [ 28 , 29 , 30 , 31 , 32 ]), and orchids (e.g., Pleurothallis [ 33 ], Trichosalpinx [ 34 ], Lepanthes [ 35 ], Pterostylis [ 36 , 37 ]) are likewise known to be visited/pollinated by Phoridae ( Megaselia ), Sciaridae ( B radysia , Corynoptera , Pseudolycoriella ), Chloropidae ( Oscinimorpha ), and Ceratopogonidae ( Forcipomyia ). Furthermore, various economically important crops (e.g., Cacao; [ 38 ]) depend on the same dipteran families and genera for pollination.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, even though artificial cross experiments have determined the cross-compatibility among species belonging to the Pistillata species (Murata et al, 2018), these Arisaema species often co-occur in apparent reproductive isolation. Pollinator specialization contributes to the reproductive isolation of these species (Kakishima et al, 2019;Kakishima et al, 2020;Matsumoto et al, 2019;Matsumoto et al, 2021;Suetsugu et al, 2021).…”
Section: Pollinator-mediated Radiation In Japanmentioning
confidence: 99%
“…Indeed, even though artificial cross experiments have determined the cross‐compatibility among species belonging to the Pistillata species (Murata et al, 2018), these Arisaema species often co‐occur in apparent reproductive isolation. Pollinator specialization contributes to the reproductive isolation of these species (Kakishima et al, 2019; Kakishima et al, 2020; Matsumoto et al, 2019; Matsumoto et al, 2021; Suetsugu et al, 2021). For example, Suetsugu et al (2021) reported that the mycetophilid fungus gnats trapped by inflorescences of the sympatric, co‐blooming, and closely related species Arisaema angustatum and Arisaema peninsulae differed significantly.…”
Section: Pollinator‐mediated Radiation In Japanmentioning
confidence: 99%
See 1 more Smart Citation
“…A maximum‐likelihood phylogenetic tree of 51 Pistillata species based on 2832 bp of four plastid DNA regions with pollination system characteristics and floral morphologies shown on the right only when information on pollination systems is available (OTUs highlighted in white circles in the phylogenetic tree). In the pie charts, green, yellow, purple, and gray slices indicate the relative frequencies of pollination by Mycetophilidae, Sciaridae, Drosophilidae, and other insects, respectively Source : Drawn based on Ohi‐Toma et al (2016), Kakishima et al (2019, 2020), Matsumoto et al (2019, 2021), Suetsugu et al (2021) [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Possible Adaptive Radiation In Arisaema Section Pistillatamentioning
confidence: 99%